Dental Erosion: Effect of Diet Drink Consumption on Permanent Dentition. (October 2022) - Samman, M.; Kaye, E.; Cabral, H.; Scott, T.; Sohn, W.
Objective: The aim of this study is to examine the effect of diet drinks on dental erosion among a representative sample of US adults. Methods: Adult dietary and dental data were analyzed from the 2003–2004 cycle of the National Health and Nutrition Examination Survey. Erosion was measured with a modified tooth wear index and was analyzed as a dichotomous variable. Cluster analysis was performed, and the cluster number was based on having a separate diet drink cluster and the R 2 values. Survey procedure and sample weights were used. Results: Most of the population (80%) had some form of dental erosive lesions. When compared with the total sample, people with erosion were more likely to be male (52.5%) and older. People with no erosive lesions were younger (42.3%) and non-Hispanic Black (21.2%). Cluster analysis resulted in 4 distinct clusters: high water, high diet drinks, high coffee/tea, and high soda. The respective percentage of individuals in each cluster who had erosion was 78.9%, 85%, 83.9%, and 76.2%, where the "high diet drinks" cluster showed the highest erosion ( P = 0.28). Logistic regression modeling showed that the "high diet drinks" cluster had increased odds of erosion (odds ratio = 1.27; 95% CI = 0.58 to 2.77) when compared with the "high water" cluster, but the relationship was not statistically significant. Conclusion: High diet drinks consumption slightly increased the odds of dental erosion among US adults, although this relationship was not statistically significant. It is thus not yet clear that dentists should recommend diet drinks, as they might be linked to systemic diseases. Further research is needed to explore more about risk factors of erosion. Knowledge Transfer Statement: The findings of this study are suggestive, though not significantly, that diet drinks may increase risk for dental erosion. While further research is needed, it is not clear that dentists should recommend these drinks as healthy substitutes for sugary drinks.